Memo on U.S. Chairmanship Priorities, 1998-2000 - U.S. Chairmanship 1998-2000 (Arctic Council Secretariat, 1998)
Communication from the U.S. Chairmanship, presenting proposed Arctic Council activities for the next two years. Communication from the U.S. Chairmanship, presenting proposed Arctic Council activities for the next two years, placing the importance on Sustainable Development, Environmental Protection, and Education, Outreach and Coordination.